2001
DOI: 10.3354/meps220073
|View full text |Cite
|
Sign up to set email alerts
|

Siderophores in marine coastal waters and their relevance for iron uptake by phytoplankton: experiments with the diatom Phaeodactylum tricornutum

Abstract: Natural marine bacteria populations collected from nearshore waters produce different types of siderophores depending on the degree of iron limitation. These siderophores can facilitate iron uptake in the marine diatom Phaeodactylum tricornutum. Water samples from 15 stations along the Italian coast of the northwest Adriatic Sea were collected and filter fractionated (3.0, 0.8 and 0.2 µm). Siderophore production in the fractions was determined using cross-feeding experiments with siderophore-auxotrophic bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
(43 reference statements)
0
32
0
Order By: Relevance
“…Bacteria produce and excrete siderophores, which scavenge iron. Diatoms are not known to produce siderophores, but genome sequence analyses identified the presence of a gene orthologue of a bacterial ferrichrome binding protein that suggests the possibility of iron (III)-siderophore utilization by P. tricornutum [56,57]. Furthermore, it was shown that P. tricornutum was able to uptake siderophores ferrioxamines B and E [58].…”
Section: Network Of Putative Interactions Between Phaeodactylum Tricomentioning
confidence: 99%
“…Bacteria produce and excrete siderophores, which scavenge iron. Diatoms are not known to produce siderophores, but genome sequence analyses identified the presence of a gene orthologue of a bacterial ferrichrome binding protein that suggests the possibility of iron (III)-siderophore utilization by P. tricornutum [56,57]. Furthermore, it was shown that P. tricornutum was able to uptake siderophores ferrioxamines B and E [58].…”
Section: Network Of Putative Interactions Between Phaeodactylum Tricomentioning
confidence: 99%
“…Iron limitation of bacterial productivity is the subject of debate (Pakulski et al, 1996;Kirchman et al, 2000), however it is known that in order to aid iron acquisition, some heterotrophic bacteria produce siderophores, which are high affinity iron(III) binding ligands (Neilands, 1995). Several marine siderophores have been characterised (Trick et al, 1983;Haygood et al, 1993;Reid et al, 1993;Martinez et al, 2000;Martinez et al, 2001;Martinez et al, 2003), and their production is ubiquitous in marine bacterial isolates (Trick, 1989;Trick and Kerry, 1992;Haygood et al, 1993;Soria-Dengg and Reissbrodt, 2001). However the presence of siderophores in seawater has not been directly confirmed, although siderophore type chelating groups have been detected in extracts isolated from seawater (Macrellis et al, 2001) and siderophores are known to have similar binding strengths to natural ligands detected in seawater (Rue and Bruland, 1995;Lewis et al, 1995;van den Berg, 1997;Gledhill et al, 1998;Witter et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A nighttime decrease in nitrate uptake was more pronounced than the decrease in ammonium uptake (15-16% and 30-36% of the daylight rates, respectively). Iron uptake may also be highly light dependent: the diatom Phaeodactylum tricornutum had higher iron uptake rates during the light period (Soria-Dengg et al 2001).…”
mentioning
confidence: 99%